The ‘evil arrow’ myths and misconceptions of cancer at Lagos University Teaching Hospital, Nigeria - Ololade, Kehinde; Alabi, Adewumi; Fadipe, Babatunde; Adegboyega, Bolanle (South Afri‪can journal of oncology, 2019)
Background: Myths and misconceptions have significant impact on the presentation and management of cancers globally. One such example includes ‘evil arrow’ myths. There is limited knowledge regarding the role of misconceptions in late presentation for management in developing countries. The percentage increase in cancers in many African countries is higher than that in developed countries. Evil arrow is the seeming attack of the enemy in a supernatural version as a result of wizardry. Aim: To evaluate the relationship of common myths and misconceptions among cancer patients, their treatment and delay of presentation to the hospital. Setting: The study was undertaken in a tertiary health facility in a cosmopolitan tropical state. Method: This is a randomised observational survey study carried out among patients and their relatives referred to the Radiotherapy Clinic of the Lagos University Teaching Hospital for treatment (a lower-income mixed metropolitan setting). A self-administered questionnaire was used. Patient consent was obtained. Data were analysed with Epi Info 2002 software and the results were presented using frequency tables and charts. Results: About 57 were patients (67%) and 28 were patients’ relatives (33%). The age distribution of participants showed 31–40 years (31.8%; 27) as the highest number, while 11–20 years (1.2%; 1) was the lowest number. A slight female preponderance of 58.8% (50) was observed. High incidence of those with the opinion that cause of cancer is unknown represented 63% (54). Over 65% of patients presented with advanced disease. The reasons for late presentation to the hospital included lack of funds in 23.5% of patients (20). Conclusion: Lack of funds, myths and misconception are main reasons why patients presented late to hospital. There is a need to emphasise debunking innumerable myths and misconceptions associated with cancer.
Keywords: openalex:import

Review of radiation oncology emergencies in Lagos University Teaching Hospital, Nigeria - Adegboyega, Bolanle; Sowunmi, Anthonia; Alabi, Adewumi; Ojifinni, Oludoyinmola Omobolade; Adenipekun, A (South African journal of oncology, 2019)
Background: Radiation oncology emergencies (ROEs) are common in metastatic or locally advanced cancer accounting for a large proportion of radiotherapy indications in poor resource settings. Aim: To review pattern, presentation and outcome of ROEs in Lagos University Teaching Hospital (LUTH) and compare with an earlier study in the northern part of the country for possible geographical variation. Setting: A retrospective review of ROE record from 2008 to 2016 in LUTH. Method: Demographic data, clinical presentation, treatment and outcomes were analysed using charts and frequency tables. Results: Total of 458 cases of oncologic emergencies were reviewed. The mean age was 52.3 years with a male-to-female ratio of 1:2.2. The majority (85%) of the patients presented in stage IV, 10% stage III and 5% stage II diseases. Spinal cord compression was the commonest presentation seen in 53.9% of cases, brain metastases in 22.1% of patients and tumour haemorrhage in 22.5% of patients. Time from the onset of symptoms to treatment was between 24 and 48 h in 16.4%, > 48 h to 1 week in 64.4% and above 1 week in 19.2%. There was a complete or significant response in signs and symptoms in 77%, no improvement in 11% and 1.1% had disease progression. Conclusion: This study showed a varied pattern of presentation in ROEs from what was obtained in northern Nigeria, with spinal cord compression being the commonest in south west Nigeria. Despite a delayed onset in treatment, radiation therapy is vital in oncology emergencies management. There is a need for accessible functional radiotherapy centres in Nigeria to combat the delays in commencing treatment.
Keywords: openalex:import

Evaluation of Three-Dimensional Conformal Radiotherapy and Intensity Modulated Radiotherapy Techniques for Left Breast Post-Mastectomy Patients: Our Experience in Nigerian Sovereign Investment Authority-Lagos University Teaching Hospital Cancer Center, South-West Nigeria - Adeneye, Samuel Olaolu; Akpochafor, Michael Onoriode; Adegboyega, Bolanle; Alabi, Adewumi; Adedewe, Nusirat; Joseph, Adedayo; Fatiregun, Omolara; Omojola, Akintayo Daniel; Adebayo, Abe; Oluwadara, Esther (The Journal of Breast Health, 2021)
This study aimed to evaluate the dosimetric properties of treatment plans obtained from three-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy techniques (IMRT) plans for left chest wall breast cancer patients.A total of 20 patients with left-sided chest wall radiotherapy were randomly selected with the dose prescriptions: 42 Gy and 45 Gy in 15 and 18 fractions, respectively. Treatment plans were obtained using 3D-CRT and IMRT for each patient. Five to seven beams were used for IMRT, while tangential beams were used for 3D-CRT. Planning target volume, Dnear-max (D2 ), Dnear-min (D98 ), Dmean, Homogeneity and Conformity Indices (HI and CI) were obtained. Similarly, mean doses to organs at risk (OAR), V5, V10, V20, V25 were generated from the dose-volume histogram and compared.IMRT showed a significant improvement in HI compared to 3D-CRT (p<0.0001). Although there was no significant difference in sparing of the left lung between both plans for high-dose volumes (V20: 18.2 vs 30.55, p<0.0001), (V25: 11.17 vs 28.12, p<0.0001). IMRT however showed supremacy to 3D-CRT with high-dose volumes for the heart, including V20 (4.44 vs 10.29, p = 0.02), V25 (2.08 vs 8.94, p = 0.002). 3D-CRT was better than IMRT in low-dose volumes for left lung (V5: 92.23 vs 56.60, p<0.001; V10: 60.98 vs 47.20, p = 0.04) and heart (V5: 57.45 vs 30.39, p = 0.004).IMRT showed better homogeneity and sparing of high-dose volumes to OAR than 3D-CRT. On the other hand, 3D-CRT showed a reduction of low-dose volumes to OARs than IMRT.
Keywords: openalex:import

Impact of 10-Day Fulbright Specialist Program and Project Pink Blue Education Sessions on Medical Oncology Knowledge Among Physicians Who Treat Cancer in Nigeria - Martin, Mike G.; Chidebe, Runcie C.W.; Nwaneri, M O; Miller, Elmer S.; Okoye, Ifeoma; Esiaka, Darlingtina; Olasinde, T; Durosinmi-Etti, F.A.; Igbinoba, Festus; Adegboyega, Bolanle; Adenjii, A; Aruah, Chinedu S.; et al. (Journal of Cancer Education, 2022)
Keywords: openalex:import